Investigation of ground moving target indication techniques for a multi-channel synthetic aperture radar - Mosito, Katlego Ernest (Department of Electrical Engineering, 2020)
Synthetic Aperture Radar (SAR) is an imaging technique that creates two dimensional images of the scattering objects in the illuminated ground scene. The objects in the illuminated ground scene may be truly stationary, e.g. buildings etc. or in motion relative to these stationary objects, e.g. cars on a highway. In SAR, the radar platform is moving during the imaging period, hence everything that the radar illuminates has motion relative to the radar platform. In order to specifically detect objects on the ground that are moving relative to stationary ground objects (often termed clutter), processing techniques called Ground Moving Target Indication (GMTI) techniques are required. This is especially required for targets that are moving at relative velocities lower than the stationary clutter's relative velocity to the radar platform (endo-clutter detection). This dissertation investigates five multichannel GMTI techniques being Displaced Phase Centre Antenna (DPCA), Along Track Interferometry (ATI), Iterative Adaptive Approach (IAA), Space Time Adaptive Processing (STAP) and Velocity SAR (VSAR) in literature and assesses the performance of two selected GMTI techniques (ATI and DPCA) on simulated and measured radar data to compare them and identify their strengths and weaknesses. The radar data were measured with a C-band FMCW radar in a controlled environment with known parameters and cooperating targets. The performances of the techniques were assessed in terms of moving target detection within clutter and sensitivity to inaccuracies in the physical system setup. The DPCA technique exhibited some attractive characteristics over the ATI technique. These included its robustness against false alarm in noise dominated cells - ATI exhibited large phase residuals in noise dominated cells, due to the random nature of the phase in these cells. Furthermore, DPCA seem to not suffer from false alarms due to volumetric scattering of vegetation to the extent that was observed with ATI. Lastly, DPCA exhibited more robustness against temporal misalignment errors introduced between the measurement channels, compared to ATI. These observations lead to the conclusion that DPCA would be a practically better choice to implement for the purpose of moving target detection, compared to ATI. However, a double threshold approach, which used DPCA as a pre-processing step to ATI, proved to be superior to DPCA alone in terms of moving target indication within clutter and noise. This approach was verified through implementation on the measured radar data in this study.